Clontuskert Augustinian Priory, interior, east window, base - O'Donovan, Danielle (My University, 2009)
Base of shaft at outer face of jamb. Moulding from top down comprises: chamfered fillet, bell with keel half way down, fillet, scroll, chamfer, plinth. This base is similar in type to those at Holycross, Kilconnell, Lorrah, Strade etc.
East window
Keywords: scroll; Architecture, Gothic -- Ireland; Galway (Ireland)--Buildings, structures, etc.; Architecture, Augustinian; Late Medieval; fillets (moldings); roll moldings; plinth; bar tracery; keel moldings